Modelling of sawtooth-induced fast ion transport in positive and negative triangularity in TCV. (4th January 2022) - Vallar, Matteo; Podestà, Mario; Baquero-Ruiz, Marcelo; Bonofiglio, Philip; Duval, Basil; Karpushov, Alexander N.; Merle, Antoine; Mikitchuk, Dmytry; Sauter, Olivier; Stipani, Lorenzo; Testa, Duccio; the TCV Team,
Abstract: Internal kinks are a common magneto hydro-dynamic (MHD) instability observed in tokamak operation when the q profile in the plasma core is close to unity. This MHD instability impacts both the transport of the bulk plasma (current, particle and energy transport) and minority species, such as fast ions. In tokamak à configuration variable (TCV) ( R 0 / a = 0.88 m/0.25 m) the fast ion population is generated in the plasma by neutral beam tangential injection of energies up to 28 keV. TCV features 16 active shaping coils permitting a great flexibility in plasma shape, including negative triangularity ( δ ) configurations that show surprisingly high confinement. This study focuses on the transport of fast ions induced by sawteeth, by comparing two triangularity cases and simulation results with experimental data. Comparison of two equilibria with opposite δ shows that the fast ion drifts are larger for δ < 0. Furthermore, the sawtooth-induced transport in this case is larger than δ > 0 in similar conditions. Comparison with experimental data confirms the dominance of the modification of thermal kinetic profiles following the sawtooth crash in explaining drops in the neutron rates and fast ion D- α signals. Additional fast ion diffusion, however, improves the interpretation of the experimental data. For δ < 0, the amplitude of the perturbation better representing the experimental data is larger. Finally, an exploratory study for 50 keV particles (soon available in TCV) shows that the situation does not worsen for such particles.